MEMBANGUN DAN MEMBERDAYAKAN MASYARAKAT Pendekatan Pekerjaan Sosial Generalis - Suradi Suradi (Sosio Informa, 2007)
Community is a complex social unity, cause have social, economic, cultural, politic, religious and enverimental dimension that affect each other. All these dimension show the complexity of the problems in the community. Therefore, in the frame of community development astrategy which is oriented to a solution of complex problems, is needed approach to this problems solution is a generalis approach, that integrated micro, messo and macro approaches in synergy, and supported by various practical principles and basic system in community development.Keyword : community empovernment, dimension and strategy.